Synthesis, structural characterisation, and cytotoxicity studies of Bi, W, and Mo containing homo- and hetero-bimetallic polyoxometalates. Issue 42 (8th October 2019) - Senevirathna, Dimuthu C.; Werrett, Melissa V.; Kubeil, Manja; Stephan, Holger; Andrews, Philip C.
Abstract : High nuclearity, water soluble polyoxometalates composed of high Z number metals W, Mo and Bi demonstrate low toxicity to human carcinoma and healthy embryonic cells and their potential as radiosensitisers. Abstract : Three new and different homo- and hetero-bimetallic polyoxometalate (POM) species have been synthesised by simple one-pot synthetic methods utilising naturally occurring bismite (Bi2 O3 ) (or Bi(NO3 )3 ·5H2 O) and aryl sulfonic acids. The POM species isolated are (NH4 )14 [Bi2 W22 O76 ]·14H2 O (1 ·14H2 O), (NH4 )[Bi(DMSO)7 ][Mo8 O26 ]·H2 O (2 ·H2 O) and [(NH4 )4 (Mo36 O108 (OH)4 ·16H2 O)]·45H2 O (3 ·45H2 O). The compounds have been characterised by X-ray crystallography, energy dispersive X-ray spectroscopy (EDX), powdered X-ray diffraction (PXRD), mass spectrometry (ESI-MS), Raman spectroscopy, thermogravimetric (TGA) and ICP analyis. In vitro cytoxicity and proliferation studies conducted on 1 and 3, highlight the low toxicity of these species.